Cells containing aragonite crystals mediate responses to gravity in Trichoplax adhaerens (Placozoa), an animal lacking neurons and synapses. - Tatiana D Mayorova; Carolyn L Smith; Katherine Hammar; Christine A Winters; Natalia B Pivovarova; Maria A Aronova; Richard D Leapman; Thomas S Reese (PLoS ONE, 2018)
Trichoplax adhaerens has only six cell types. The function as well as the structure of crystal cells, the least numerous cell type, presented an enigma. Crystal cells are arrayed around the perimeter of the animal and each contains a birefringent crystal. Crystal cells resemble lithocytes in other animals so we looked for evidence they are gravity sensors. Confocal microscopy showed that their cup-shaped nuclei are oriented toward the edge of the animal, and that the crystal shifts downward under the influence of gravity. Some animals spontaneously lack crystal cells and these animals behaved differently upon being tilted vertically than animals with a typical number of crystal cells. EM revealed crystal cell contacts with fiber cells and epithelial cells but these contacts lacked features of synapses. EM spectroscopic analyses showed that crystals consist of the aragonite form of calcium carbonate. We thus provide behavioral evidence that Trichoplax are able to sense gravity, and that crystal cells are likely to be their gravity receptors. Moreover, because placozoans are thought to have evolved during Ediacaran or Cryogenian eras associated with aragonite seas, and their crystals are made of aragonite, they may have acquired gravity sensors during this early era.